A biomass-derived safe medium to replace toxic dipolar solvents and access cleaner Heck coupling reactions. Issue 1 (25th September 2014) - Strappaveccia, Giacomo; Ismalaj, Ermal; Petrucci, Chiara; Lanari, Daniela; Marrocchi, Assunta; Drees, Martin; Facchetti, Antonio; Vaccaro, Luigi
Abstract : γ-Valerolactone (GVL) is an excellent reaction medium, derived from biomasses, which can replace classic dipolar aprotic media such as DMF or NMP. Abstract : γ-Valerolactone (GVL) is an excellent reaction medium, derived from biomasses, which can replace classic dipolar aprotic media such as DMF or NMP. In this contribution, we have investigated the use of GVL in the palladium-catalyzed Heck reaction and accessed the clean synthesis of several small molecules. Furthermore, we optimized a GVL-based protocol to synthesize a poly(phenylenevinylene) (PPV) derivative in high yields and purity, and with very low Pd-content. Finally, we demonstrated that GVL is superior to conventional dipolar media in terms of controlling palladium impurities, which may influence the performance of certain optoelectronic devices such as organic solar cells and field-effect transistors.